Nicotine Adds Risk Factors to the Cardiovascular System and Increases Mortality and Sudden Cardiac Arrest (Medico Legal Update, 2020)
The Work began on 7th of January 2019 and for 9 months in General Academic Hospital and SpecializedCenter for Diabetes and Chronic Diseases on smokers patients in Iraq collecting patient history and durationof smoking (modern, chronic smoking) and on non-smokers and patients. After the collection of analyzesmore patients than the First Group: of young patients older than> 25 years suffer from tension headache,polycythemia (Increased hemoglobin blood ), Psychology, variant angina, Hypertension, respiratory disease,high triglyceride (TG), shortness of breath so the effect of smoking, pollution and nicotine on patientswith chronic youth were evident smoking results : 30% of them have arrhythmias 15% increased Lipid (LDL,HDL, TG, Cholesterol), 10% psychology, 10% polycythemia (Increased hemoglobin blood ), 10%Coronary disease, 20% Respiratory diseases, 5% High blood pressure, 5% depression. The Second Group:are older than> 40 years of chronic smoking and are suffering from atherosclerosis and high blood pressure,Ischemic heart disease, Respiratory diseases in addition to malignant tumors of the lung, heart rhythmdisorders, polycythemia, Pulmonary heart disease, The appearance of cancerous tumors inside the mouth andlip, ( MI) myocardial infarction , ACD ( Acute coronary syndrome), So the results were: 20% Arrhythmias,10% coronary artery disease, 3% polycythemia (Increased hemoglobin blood), 25% chest and respiratorydiseases, 9% drug-resistant diabetes, 3% lung and oral cancers, 2% ASD, MI, 18% Increased lipid, 5%depression, In addition to emergencies sudden cardiac death that require the patient to enter Intensive CareUnit and the work of cardiac catheterization to ensure patient safety. Compared to people 65 patient who donot smoke cigarettes there is no aggravation of risk factors and a threat to people’s lives directly. Patients areunder control of their risk factor Leading to death.